Who benefited the most?: effectiveness of a lifestyle intervention against cognitive decline in older women and men : secondary analysis of the AgeWell.de-trial - Wittmann, Felix; Pabst, A.; Zülke, A.; Luppa, M.; Blotenberg, I.; Cardona, M. I.; Bauer, A.; Fuchs, S.; Zöllinger, I.; Sanftenberg, L.; Brettschneider, C.; Döhring, J.; et al. (The journal of prevention of Alzheimer's disease, 2024)
Introduction: Differences between women and men matter in the prevalence and risk factors of dementia. We aimed to examine potential sex differences regarding the effectiveness by running a secondary analysis of the AgeWell.de trial, a cluster-randomized multicenter multi-domain lifestyle intervention to reduce cognitive decline. Methods: Intention-to-treat analyses of women (n=433) and men (n=386) aged 60 to 77 years were used for models including interactions between intervention group allocation and sex followed by subgroup analysis stratified by sex on primary and secondary outcomes. Further, the same procedure was repeated for age groups (60–69 vs. 70–77) within sex-specific subgroups to assess the effectiveness in different age groups. Trial registration: German Clinical Trials Register (ref. number: DRKS00013555). Results: No differences were found between women and men in the effectiveness of the intervention on cognitive performance. However, women benefitted from the intervention regarding depressive symptoms while men did not. Health-related quality of life was enhanced for younger intervention participants (60–69 years) in both women and men. Conclusion: The AgeWell.de intervention was able to improve depressive symptoms in women and health-related quality of life in younger participants. Female participants between 60 and 69 years benefited the most. Results support the need of better individually targeted lifestyle interventions for older adults.
Veröffentlicht: 15. Januar 2024